Literature review: Analysis of the implementation at the public health center management information system - Farhanni, Nadya; Nugroho, Adi; Ringoringo , Harapan Parlindungan; Istiqomah , Ermina; Hartoyo, Edi (Institute of Computer Science (IOCS), 2025)
This study is to evaluate and examine papers concerning the examination of the installation of the puskesmas management information system. The writing method used is a literature review with the type of Systematic Literature Review (SLR) which is carried out systematically and sourced from previous research. The databases used in the literature search were Google Scholar and Garuda Portal. There were 5 articles that met the inclusion criteria and were assessed using Duffy's Critical Appraisal Approach. Based on the 5 articles obtained, 5 articles discussed the implementation of the puskesmas management information system. 5 articles discuss SIMPUS's very important role in data processing, and overall the article (100%) states the result that SIMPUS plays a very important role in data processing, and 4 articles discuss the use of SIMPUS has been said to be effective in medical record services at puskesmas, and overall (100%) the article states the result that the use of SIMPUS has been said to be effective in medical record services at puskesmas. And overall (100%) the articles state the results that software, public facilities, human resources and officer behavior can hinder the implementation of the puskesmas management information system, which is supported by several journals that discuss the implementation of the PHC management system.